OPPORTUNITY FOR CAPITAL PARTICIPATION AND GRANTS IN PDAM TIRTA WAESAI, BARRU REGENCY (STUDY ANALYSIS OF REGIONAL FINANCIAL CAPABILITIES AND PDAM CAPABILITIES) - Siswanto, Adi; Mariana, Lina; Dakhri, M. (Jurnal Ekonomi Balance, 2020)
This type of research uses a combination research method. Namely by combining quantitative and qualitative research methods. Data analysis techniques are the SWOT analysis method, regional financial capacity analysis (KKD), regional capability level analysis and Full Cost Recovery (FCR) analysis. The results showed: 1) PDAM Barru Regency Program Plan after obtaining capital participation from the Regional Government of Barru Regency is a) plan for funding activities for urban drinking water grant, free water connection for low-income communities (MBR), b) provision of water meters, c) construction of intake wells, d) construction of pump housings, e) installation of 5lt / sec cap intake pumps, f) procurement of Ø 6 ”GIP pipes, intake pumps and accessories, g) roof rehabilitation and additional space for Marolly installation operation houses and h) land acquisition Marolly intake well., 2) Regional Financial Capability of Barru Regency in distributing grant assistance in the form of Equity Participation to PDAM Barru Regency and 3) PDAM Barru Regency contribution to Regional Original Revenue is the contribution of PDAM Barru Regency to Barru Regency Government if Regional Government Capital Participation is implemented namely assisting the government in achieving Sdg's 100-0-100 targets and achieving SPM 100%. ak ses clean water.